The skeleton and movement - Dineen, Jacqueline (Englewood Cliffs, N.J. : Silver Burdett Press, 1988)
Describes the structure and function of the different parts of the human skeleton and how it is able to move with the aid of a system of muscles. Also discusses muscular and skeletal disorders and their treatment.
Includes index.
Booklist.
Wilson's Junior High School.
5.2
5-8
Keywords: Human locomotion -- Juvenile literature; Skeleton -- Juvenile literature; Muscular system; Skeleton; Musculoskeletal system; Skeleton